Impact of institutional support on export performance - Mário Nuno Mata; Mohammad Falahat; Anabela Batista Correia; Jo\~ao Xavier Rita (Economies, 2021)
This paper examines institutional support (financial and marketing support) on export-oriented firms' performance or so-called born globals. We develop a model to address how financial and marketing support can help young entrepreneurial firms to overcome the liability of newness and smallness in gaining competitive capabilities. Using a quantitative method, data were collected from 217 manufacturers and service sectors in Malaysia, an emerging Southeast Asian market. The results suggest that government assistance in marketing leads to competitive capabilities and export performance; however, financial support neither contributes to competitive capabilities nor export performance. We found the significant role of competitive capabilities as a mediator in enhancing the relationship between marketing support and export performance. Practical implications drawn from this result can be offered as guidelines for the policymakers in supporting young entrepreneurs that lead to competitive capabilities and superior performance.
Keywords: 330; institutional support; government assistance; export assistance; financial support; marketing support; competitive capabilities; export performance